2012
DOI: 10.1016/j.psyneuen.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and hormonal sensitivity to threat: Testing a serotonin transporter genotype×testosterone interaction

Abstract: Summary Background Striking parallels are observed when comparing the literature on the 5-HTTLPR of the serotonin transporter gene (SLC6A4) to the testosterone (T) literature on measures of stress reactivity and neural activity. Short (S) allele carriers and individuals higher in testosterone levels show exaggerated stress responses, amygdala hyperactivity, and reduction of amygdala-prefrontal cortex coupling when exposed to threat. Methods Three studies tested the hypothesis that higher T, S carriers would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Following informed consent, participants provided demographic information, completed questionnaires, and were interviewed for the presence of diagnoses based on the fourth edition, text revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR; American Psychiatric Association, 2000). Study procedures included a number of assessments that are not the focus of the current study but are reported elsewhere Beevers, Marti, et al, 2011;Josephs et al, 2012;Telch et al, 2013;Telch, Rosenfield, Lee, & Pai, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Following informed consent, participants provided demographic information, completed questionnaires, and were interviewed for the presence of diagnoses based on the fourth edition, text revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR; American Psychiatric Association, 2000). Study procedures included a number of assessments that are not the focus of the current study but are reported elsewhere Beevers, Marti, et al, 2011;Josephs et al, 2012;Telch et al, 2013;Telch, Rosenfield, Lee, & Pai, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Examining the concomitant effects of another polymorphism (C1019G) from the serotonin receptor gene, 5HT1A and the Val66Met polymorphism of the BDNF gene revealed increased risk for depression when expressing both risk variants (61). In addition, carriers of the long allele with concomitant higher levels of testosterone showed lower cortisol secretion after threat indicating neuropsychiatric resilience for this combination in humans (62). A recent review on genetic association studies of suicidal behavior identified 5HTTLPR and BDNF among few others as most promising candidates (63).…”
Section: Genetic Risk Constellationmentioning
confidence: 99%
“…Testosterone is believed to exert neurotrophic effects, proposed to occur via aromatization to estradiol and/or by transformation into 5α-dihydrotestosterone [28]. Furthermore, testosterone is implicated in serotonin activation [54], and baseline testosterone is known to interact with 5HTTLPR S carriage to augment cortisol response to heterogeneous threats [55]. Clearly, potential roles of 5HTTLPR and prior trauma exposure in regulating testosterone stress response require further investigation.…”
Section: Discussionmentioning
confidence: 99%